Yogyakarta Mayor Herry Zudianto's Success Strategy (2001-2011) In Implementing Bureaucratic Reforms to Realize Good Governance) - Abdul Fikri Wisudawan Siregar (Trigin Publisher, 2021)
Religious pluralism seems to have met its golden age again. At a time when Indonesian people often have conflicts with religious nuances, the discussion of pluralism will again become a topic of conversation among interfaith leaders in Indonesia. In this case, the author will try to review the meaning of pluralism according to one of the moderate figures in Islam, namely Hasyim Muzadi, Rois Syuriah, the Executive Board of Nahdlatul Ulama. The study of Hasyim Muzadi's religious pluralism in this thesis is based on the background that the author considers that so far there are still few works that contain Hasyim Muzadi's thoughts. The author's aim is to deepen the knowledge of Hasyim Muzadi's thoughts on pluralism and the steps he took to fight for religious plurality in Indonesia. Hasyim Muzadi as one of the moderate figures who consistently fights for Pluralism, offers a solution to the impasse of dialogue between religions and beliefs. Pluralism is considered a necessity to maintain religious plurality in Indonesia and maintain harmony between people of different religions and beliefs so as to strengthen the integrity of the Unitary State of the Republic of Indonesia. Conclusion from the discussion of Hasyim .'s thoughts Among other things, Muzadi thought about Pluralism as part of Humanism and the differences between theological pluralism and sociological pluralism. According to Hasyim Muzadi, religious people in Indonesia must be aware that the problems they have faced so far are the deadlock of dialogue between groups with different interpretations of the religious teachings they profess. So according to the author, this discussion is very important to re-awaken the understanding of religious pluralism with the aim of creating harmony among religions and between religions even though differences in belief and religion are a necessity in the life of this pluralistic nation and state.